Analyzing the effect of household income on female labor force participation in the context of educational attainment, marital status, and urbanization - Custodio, Bryan A.; Mozo, Anjelalie B.
The study investigates the relationship between Female Labor Force Participation (FLFP) and household income (HI) and examines how this relationship varies with educational attainment, marital status, and urbanization. The main hypothesis is that while a negative relationship exists between HI and FLFP, the magnitude, direction, and/or other dimensions of this relationship are affected by a woman's marital status, educational attainment, and urbanization. To test this hypothesis, the study estimates five distinct binomial probit models to test the inclusion of variables of interest and their interaction terms with total household income in relation to FLFP, using the most recent 2018 merged data from the Labor Force Survey (LFS) and Family Income and Expenditure Survey (FIES). It is found that without the inclusion of education, marital status, and urbanization, the probability of women joining the labor force increases with household income but at a decreasing rate. Meanwhile, when education is taken into account, the impact of household income on female labor force participation (FLFP) is entirely negative. However, in this model, higher-income households tend to experience a greater positive effect from education in terms of FLFP. Urbanization and marital status were not found to have any strong effect on the direction of the relationship of household income to FLFP. However, urban and marital status did have effects on the slope, with the effect being stronger for married individuals than those not married. Ultimately, this study provides insights into the factors that negatively affect and positively contribute to the labor force participation of women in the Philippines, allowing policymakers to design targeted interventions that address barriers and strengthen facilitators of women's participation in the labor force and promote inclusive development that addresses the issue of gender disparity.